A software to prevent delirium in hospitalised older adults: development and feasibility assessment. (20th January 2020) - Alvarez, Evelyn A; Garrido, Maricel; Ponce, Daniela P; Pizarro, Gaspar; Córdova, Andres A; Vera, Felipe; Ruiz, Rocio; Fernández, Raul; Velásquez, Juan D; Tobar, Eduardo; Salech, Felipe
Abstract: Background: non-pharmacological interventions to prevent delirium are useful in hospitalised older adults. However, they are poorly implemented in clinical practice. We aimed to develop a software for bedside use by hospitalised older adults and to improve their access to these interventions. Methods: a transdisciplinary team composed of healthcare professionals, designers, engineers and older adults participated in the development of the software. Scrum methodology was used to coordinate the work of the team, and the software was evaluated in a feasibility study. Results: a software for touchscreen mobile devices that supports Android 5.0 or later was produced, including modules for time-spatial re-orientation, cognitive stimulation, early mobilisation, sensorial support use promotion, sleep hygiene and pain management optimisation. Horizontal disposition, use of colour contrast and large interaction areas were used to improve accessibility. The software's usability and accessibility were evaluated in 34 older adults (average age 73.2 ± 9.1 years) showing that 91.1% of them got access to all the software functions without previous instructions. The clinical feasibility assessment showed that 83.3% of the 30 enrolled hospitalised patients (76 ± 8 years) completed the 5-day protocol of software usage during hospitalisation. Software use was associated with a decreased trend in delirium incidence of 5 of 32 (15.6%) at baseline to 2 of 30 (6.6%) after its implementation. Conclusion: a highly accessible and implementable software, designed to improve access to non-pharmacological interventions to prevent delirium in hospitalised older adults, was developed. The effectiveness of the software will be evaluated in a randomised clinical trial.